Electro growth of Al-Cu eutectic alloy - Basit, Sercan; Birinci, Semih; Marasli, Necmettin (ELSEVIER SCIENCE INC, 2020)
The effects of directions and magnitudes of static electrical field on solidification of Al-33 wt.%Cu eutectic alloy were investigated. For this purpose, a new directional solidification apparatus was specially designed to solidify the Al-Cu eutectic alloy under static high electrical field (E). For the first time, the Al-Cu molten eutectic alloy was solidified under different directions; parallel and antiparallel of the solid liquid interface growth direction (E+ and E_, respectively) and magnitudes (7-10 kV/cm) of static high electrical fields. The lamellar spacing (lambda), eutectic grain size (EGS) and hardness (HB) of the Al-Cu eutectic alloy solidified with different values of E+, and E_ were measured with standards methods. It was observed that the static electrical field is an effective control parameter on the directional solidification and the values of lambda, EGS and HB are increased and decreased with increasing the values of E+ and E_, respectively in the Al-Cu eutectic alloy. Finally, the dependency of EGS and HB values on E+ and E_ values were obtained with linear regression analysis in the Al-Cu eutectic alloy.
Keywords: Solidification under electric field; Aluminium-copper alloy; Microstructure; Grain size; Hardness; LAMELLAR; FIELD; SOLIDIFICATION; SELECTION; Materials Science; Metallurgy & Metallurgical Engineering